Factores asociados al ausentismo laboral por descansos médicos de los trabajadores de la empresa de tercerización Representaciones Agromaster S.A.C. de enero a julio del 2015. - Bringas Pérez, Karen Noelia (2017)
INTRODUCTION.- Absenteeism is "non-appearance of the worker to his job position in hours that should really be," being caused by various factors such as health and others that exist in the workplace. This study aimed to determine what factors are associated with Medical-Absenteeism Labor breaks by Company personnel Representations Outsourcing AGROMASTER S.A.C. from January to July 2015. METODOLOGY.-. The investigation, was descriptive, the sample was 187 workers distributed 82 stevedoring, 24 coupling and uncoupling of wagons, 69 and 12 cleaning field production control. RESULTS.-Factor greater incidence in the absence of workers was indifferent or weak institutional identification with 61.5%, unlike working hours and working environment, where they found according to 83.4% and 75.9% respectively. The total absences was 54%, while 60% used a medical leave to justify their absence; being the causes: 44% due to fatigue, boredom 22%, 19% had other reasons and 15% by listlessness. 72% of workers were absent one day, while most was the work of stevedoring with 43.9%. DISCUSSION.- Institutional identification was indifferent or poor, not to belong to the agricultural system depends on a user undertaking. The incidence in agroindustrial field work involving the worker to exhaustion and fatigue justified, it is confirmed in the presentation of medical leaves the workplace for a day, used to justify the absence and avoid being sanctioned and economically disadvantaged. CONCLUSIONS.- Weak institutional identification if I generate significant influence on the relationship breaks doctors - unlike absenteeism inadequate working hours and working environment that is not influenced.